Association between diastolic dysfunction of the left ventricle and pulmonary hypertension in inhabitants of rural andean: diastolic dysfunction - Díaz-Lazo, Aníbal Valentín (2022)
Objectives: To determine the association between left ventricular diastolic dysfunction (LVDD) and pulmonary hypertension (PH) in rural Andean patients living at high altitude. Material and methods: observational, cross-sectional analytical study. PH and LVDD were defined and evaluated according to the guidelines of the American Society of Echocardiography. To evaluate the association, the generalized linear Poisson model with robust estimation was used. A value of p < 0.05 is significantly estimated. Results: 528 (100%) people with echocardiographic reports were included, with a median age of 67 years (interquartile range: 19 and 98), 58.71% (310) were women. LVDD was found in 20.5% (108) of the cases. The frequency of PH was 29.5% (154), corresponding to a mild, moderate and severe degree in 76.0%; 14.3% and 9.7% respectively. Simple regression analysis reported that people with LVDD, obesity and E/e' ratio > 14 had a higher frequency of PH compared to those without LVDD. In the multiple regression, an association was found between LVDD (RPa= 0.17; 95% CI: 0.11-0.24; p = 0.000) and the E/e' index > 14 (RPa= 1.93; 95% CI: 1, 27-2.91, p = 0.002) in people with PH. Conclusions: LVDD and the E/e' index are frequently associated with PH in Andean inhabitants of rural areas, suggesting that the presence of alterations in the relaxation and distensibility of the left ventricle is  associated with PH.